2021
DOI: 10.3390/jpm11090828
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Bladder Cancer in Type 2 Diabetes Mellitus with Combination Therapy of SGLT-2 Inhibitors and Pioglitazone

Abstract: Background: Either sodium-glucose cotransporter-2 (SGLT-2) inhibitors or pioglitazone (Pio) has doubtful issues of bladder cancer, especially for the combination therapy with these two drugs. Our study aimed to investigate the risk of bladder cancer under combination therapy of SGLT-2 inhibitors and Pio. Materials and Methods: We included 97,024 patients with type 2 diabetes mellitus (T2DM) in the Chang Gung Research Database in Taiwan from 1 January 2016 to 31 December 2019. The primary outcome was newly diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…33 However, several recent studies have reported the absence of any significant association between SGLT-2i use and the risk of bladder cancer. 29,49,50 This finding indicates that evidence on the relationship between SGLT-2i use and the risk of bladder cancer remains inconclusive, possibly because of differences in studies' design, such as differences in follow-up periods, control group settings, and ethnicities of participants. Additionally, the side effects of SGLT-2is, such as an increased risk of urinary tract infection, could have increased the likelihood of urinary tract cancer being detected early in randomised trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 However, several recent studies have reported the absence of any significant association between SGLT-2i use and the risk of bladder cancer. 29,49,50 This finding indicates that evidence on the relationship between SGLT-2i use and the risk of bladder cancer remains inconclusive, possibly because of differences in studies' design, such as differences in follow-up periods, control group settings, and ethnicities of participants. Additionally, the side effects of SGLT-2is, such as an increased risk of urinary tract infection, could have increased the likelihood of urinary tract cancer being detected early in randomised trials.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis conducted on 46 randomised controlled trials revealed that the risk of bladder cancer was nearly four times higher in patients who took an SGLT‐2i than in those who did not 33 . However, several recent studies have reported the absence of any significant association between SGLT‐2i use and the risk of bladder cancer 29,49,50 . This finding indicates that evidence on the relationship between SGLT‐2i use and the risk of bladder cancer remains inconclusive, possibly because of differences in studies' design, such as differences in follow‐up periods, control group settings, and ethnicities of participants.…”
Section: Discussionmentioning
confidence: 99%
“…4,[22][23][24] However, numerous studies have reported the incidence of cancer, especially bladder cancer, after treatment initiation. 13,[25][26][27] Those studies generated confusing results and we could not confirm the causal association between SGLT2 inhibition and cancer incidence. Recently, three original studies explored the same topic.…”
Section: F I G U R Ementioning
confidence: 91%
“…Recently, three original studies explored the same topic. 13,25,26 One extracted data from European pharmacovigilance database 26 and concluded that SGLT2 inhibitors could increase the risk of bladder cancer in sensitive analysis (OR: 6.84, 95%CI: 5.41-8.65). While the other two did not report the risk of bladder cancer incidence compared with placebo or positive controls, 13,25 the follow-up year was relatively short (<3 years).…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation